PENGEMBANGAN MEDIA INTERAKTIF BERBANTUAN CANVA DENGAN MODEL PBL UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA MATERI RANTAI MAKANAN DI KELAS V SD - Girsang, Farhan Alfath; Hidayat, Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research conducted aims to develop an interactive media assisted by Canva using the PBL model to increase students' interest in learning food chain material in grade V of elementary school. This research is a Research and Development (R&D) study conducted using the 4D development procedure. To collect the required data, the researcher used a validation questionnaire given to several expert validators and a student learning interest questionnaire to measure students' interest in learning before and after using the developed media. From the results of the media expert validation, a validity score of 84 was obtained with the criteria